\[y{d^2y \over dx^2}+1=({dy \over dx})^2\]

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

\[y{d^2y \over dx^2}+1=({dy \over dx})^2\]

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

the equation is x-absent
y y'' +1= (y')^2 (y'y)'=y'' y+ (y')^2
i can not see how you did that

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

that's not quite right since y'' y+ (y')^2 and we want y'' y- (y')^2
let\[y'=p\]\[y''=pp'\]
can you please retype your equation it's confusing me
can you please retype your equation it's confusing me
can you please retype your equation it's confusing me
can you please retype your equation it's confusing me
can you please retype your equation it's confusing me
can you please retype your equation it's confusing me
can you please retype your equation it's confusing me
ok
\[y=y(x)\]\[y{d^2y \over dx^2}+1=({dy \over dx})^2\]or\[y{y''}+1=(y')^2\]
\[ypp'+1=p^2\]
\[p'+{1 \over py} = {p \over y}\]
Differentiate your equation wrt x and we have \[ y'y'' + yy''' = 2y'y'' \] i.e., \[ yy''' = y'y'' \] or \[ \frac{y'''}{y''} = \frac{y'}{y} \] Now integrate wrt to find \[ \ln(y'') = \ln(y) + C \] or \[ y'' - Ay = 0 \] for a positive constant \( A (= -e^C) \). The solutions of this are now easy to find and you can see they satisfy the original ODE. Notice that if you not take A to be positive, you wind end with sin and cos as a basis for the solution space, and those functions do not satisfy the original ODE.
*correction: A = +e^C
the answer in the back of my book is \[┬▒cln(y+\sqrt{y^2+c^2} = x +d\] where c and d are the constants
The thing on the left looks like arccosh, so that makes sense to me. I'm trying to figure out though where they get two constants from.
well we have y''=... so integration twice will produce the two constants
right?
Yes, I know in general a second order _linear_ equation has a 2-dimensional solution space. And having two parameters here is also consistent. I'm just trying to figure out where I lost one it in the solution.
Ok. So writing more carefully, we have \[ y'' - \lambda^2 y = 0 \] and two possible Ansatz are \[ y_1(x) = A \cosh(\lambda (x-x_0)) \] \[ y_2(x) = B \sinh(\lambda (x - x_0)) \] Now, it's not hard to show y_2 can't satisfy the original equation, and y_1 satisfies it if and only \[ A^2 \lambda^2 \cosh^2(\lambda(x-x_0)) + 1 = A^2 \lambda^2 \cosh^2(\lambda(x-x_0)^2) \] i.e., \[ A = 1/\lambda \] Hence it appears one 2-parameter family of solutions is \[ y_{(\lambda,x_0)}(x) = \cosh(\lambda(x-x_0)) \]
I know this procedure is somewhat unsatisfactory and feels a bit arbitrary. Part of that, I think, is the nature of non-linear ODEs. I suppose we can call on the Picard theorem to convince ourselves there aren't more solutions.
bleah ... that equation 2 posts above should stuff . cosh^2 + 1 = stuff . sinh^2
i got lost

Not the answer you are looking for?

Search for more explanations.

Ask your own question